Karakteristik Temperatur Pada Permukaan Sel Surya Polycrystalline Terhadap Efektifitas Daya Keluaran Pembangkit Listrik Tenaga Surya - Andi Makkulau; Samsurizal Samsurizal; Salvatore Kevin (Sekolah Tinggi Teknik - PLN, 2020)
Devices that can convert sunlight energy to electrical energy with photovoltaic effect process made of semiconductors are better known as solar cells. Photovoltaic (PV) or better known as solar power plant (PLTS) is also concerned with several factors to maximize solar energy into electrical energy such as the influence of weather, humidity, temperature of solar cell position and wind direction contained on the surface of solar cells. In this study, this solar cell (photovoltaic) was diagnosed as poly-crystalline during sunny and cloudy weather conditions. The results obtained by the test showed the influence of temperature from the surface of solar cells on the value of output power. Maximum power (Pout) at 11.40 WIB with a slope angle of 35° and a temperature of 47.6°C with an output power value of 100.562 Watt. So it can be said that the temperature is influenced by the intensity of solar radiation that will make the power (Pout) increase, the condition of the poly-crystalline solar module will work optimally at a temperature of about 35 °C - 50 ° C measured on the surface of solar cells.